5G Patent Licensing in Industrial Internet of Things : An analysis of patent licensing design criteria for future licensing of 5G in the segment of Industrial Internet of Things - Harder, Leonard; Larsson, Henrik (My University, 2022)
The global trend of Internet of Things is spreading into the industrial sector, driven of gains in efficiency and cost reduction. Wireless technologies lay the foundation of IoT and 5G has the possibility to enable new use-cases for the industry. An effective licensing solution is requested to help spread the adoption of the technology while also incentivizing further research and development in cellular technology. The aim of this thesis is to investigate and evaluate design criteria of such a solution. This is important as it is likely to increase adoption rate and lower transaction cost associated with acquiring technology licenses for 5G. This in turn also supports innovation. The study was conducted in two parts consisting of a literature review and a series of semi-structured interviews respectively. The interviewees represented telecom companies, IIoT OEMs, manufacturing companies, academia and licensing entities. The study also analyses the case of automotive IoT licensing of Avanci and analyses its transferability to the case of IIoT. The results collected were then triangulated and analyzed, and conclusions were drawn. The study concluded that 5G contributes a lot of value to IIoT, especially within low latency and high reliability applications. Furthermore, a patent pool is likely a suitable solution, primarily due to the market characteristics of IIoT. These characteristics include, but are not limited to, the numbers of both SEP holders and implementers, and their desire to have a transparent, predictable, and simple licensing arrangement.
Keywords: 5G; IIoT; patent licensing; patent pool; automotive